Megaptera novaeangliae - Thu, Aye Myat; Lwin, Ye Htet; Quan, Rui-Chang (Zenodo, 2024)
340. Megaptera novaeangliae (Borowski, 1781) Common name: Humpback Whale Myanmar name: Distribution: Worldwide distribution from cold-temperate to tropical waters. In Myanmar, recorded in the offshore waters of Bay of Bengal (Parnum 2019). Published as part of Thu, Aye Myat, Lwin, Ye Htet & Quan, Rui-Chang, 2024, Mammals of Myanmar: an annotated checklist, pp. 147-197 in Mammalia (Warsaw, Poland) (Warsaw, Poland) 88 (3) on pages 189-190, DOI:10.1515/mammalia-2023-0098, http://zenodo.org/record/13913939